(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
Corporate governance has the great concern from the international and regional, institutions and organizations especially after the current financial crisis. It became a fertile field for research and study. So an urgent need was to do research links the relationship between taxes and corporate governance to take advantage of Its multiple positives because corporate governance helps in the elimination of the conflict, to achieve harmony and balance between the interests of different groups interested in the company whether from within or from outside, financial authority is one of the these categories. The aim of this research is to achieve a set of objectives including: make use of the application of the rules of corporate governance in companies through some mechanisms to improve the accounting information contained in financial reporting. Determining the impact of application of the rules of corporate governance in the credibility of financial reporting and to enhance confidence in the reports submitted to the General Commission for Taxes in the determination of tax fairly.